Calibration and verification of areal surface texture measuring instruments. Issue 2 (2015) - Leach, R.K.; Giusca, C.L.; Haitjema, H.; Evans, C.; Jiang, X.
Abstract In this paper, the calibration and verification infrastructure to support areal surface texture measurement and characterisation will be reviewed. A short historical overview of the subject will be given, along with a discussion of the most common instruments and directions of current international standards. Traceability and uncertainty will be discussed, followed by a presentation of the latest developments in software and material measurement standards. The concept and current infrastructure for determining the metrological characteristics of instruments will be highlighted and future research requirements will be presented.